Minimal runnable package for “An Interpretable Vibration-Enhanced BRB Model for Rolling Bearing Fault Diagnosis” - Ziyu Fan (22586633) (2025)
This archive provides the minimal runnable MATLAB project and processed datasets used in the paper “An Interpretable Vibration-Enhanced BRB Model for Rolling Bearing Fault Diagnosis”. It includes all scripts (main.m and auxiliary functions), training/testing subsets, and a README file describing the file structure and usage. This dataset enables reproducibility of the experimental results.